The Culture of Bayar Harta Kepala During Grieving Process of Sentani Tribe - Yemima Costanpina Wasanggay; Berta Esti Ari Prasetya (International Journal Labs, 2023)
Grieving is a natural human response when losing a loved one, but a prolonged grieving process can interfere with daily functioning that needs clinical intervention. An individual's sense of grief can be influenced by various aspects, one of which, is the culture and traditions carried out when grieving. One of the prominent cultures of grieving comes from the people of Sentani, called yung robboni or bayar harta kepala. This culture requires the payment of property by the bereaved family to the birth mother’s family who comes to give food. This may feel burdensome for individuals with a low socioeconomic level and can affect the grieving process that is felt as well. Therefore, this study aims to explain how the people of Sentani interpret the grieving process in the culture of bayar harta kepala. The research was conducted using qualitative methods with a narrative approach. Research participants were obtained by purposive sampling, namely with the criteria of adult individuals aged 23-55 years who have middle to lower economic status, have deceased relatives, and carry out the tradition of bayar harta kepala. Two participants were obtained, one was a female individual aged 54 years old (MT), and the other was a female, aged 46 years old (A). The results showed that the culture of bayar harta kepala, although economically burdensome, was seen as a means of obtaining social support from the family, thus alleviating the grief that was felt. Overall, this study emphasizes the importance of empowering a culture of bayar harta kepala, followed by social and family support, in overcoming individual grief.